2002
DOI: 10.1152/ajpheart.00222.2002
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal tissue oxygenation and microvascular flow motion during hemorrhage and resuscitation

Abstract: tissue oxygenation and microvascular flow motion during hemorrhage and resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…Cardiac index, PAOP, and tissue oxygen tension of the jejunum after hemorrhage in a recent study in pigs [17] reacted comparably to our study. However, MAP did not decrease significantly after 15% of blood loss in Pajk's study [17], while MAP decreased significantly after 10% of blood loss in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Cardiac index, PAOP, and tissue oxygen tension of the jejunum after hemorrhage in a recent study in pigs [17] reacted comparably to our study. However, MAP did not decrease significantly after 15% of blood loss in Pajk's study [17], while MAP decreased significantly after 10% of blood loss in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, MAP did not decrease significantly after 15% of blood loss in Pajk's study [17], while MAP decreased significantly after 10% of blood loss in our study. Probably the different anesthesia technique (total intravenous anesthesia in Pajk's study versus isoflurane anesthesia in our study) contributed to this difference.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Several studies have demonstrated that infusion of dopamine (or its agonists) during hemorrhage or following resuscitation improves tissue oxygenation in the splanchnic circulation [141,142] . Dopamine also prevents rhythmic oscillations in blood flow during hemorrhage that apparently contributes to reduced oxygenation [142] .…”
Section: Physiological Actions In the Microcirculationmentioning
confidence: 99%